2020
DOI: 10.1371/journal.pone.0224052
|View full text |Cite
|
Sign up to set email alerts
|

Testicular toxicity following chronic codeine administration is via oxidative DNA damage and up-regulation of NO/TNF-α and caspase 3 activities

Abstract: BackgroundCodeine, a 3-methylmorphine, and other related opioids have been implicated in androgen suppression, although the associated mechanisms remain unclear. AimTherefore, the objective of the current study was to elucidate the in vivo molecular mechanisms underlying codeine-induced androgen suppression. MethodsThis study made use of twenty-one healthy male rabbits, distributed into three groups randomly, control and codeine-treated groups. The control had 1ml of normal saline daily p.o. The codeine-treate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 62 publications
7
68
0
Order By: Relevance
“…Despite the increases in incidences of male factor infertility of unknown causes and codeine abuses, data reporting the impact of codeine on male reproduction remains scarce. Although in our previous studies, we demonstrated that oral codeine exposure in rabbits impaired fertility indices [30], and led to testicular degeneration and testosterone suppression [46]. This present study is an extension of our previous studies on [30,46] and data sets were obtained separately.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Despite the increases in incidences of male factor infertility of unknown causes and codeine abuses, data reporting the impact of codeine on male reproduction remains scarce. Although in our previous studies, we demonstrated that oral codeine exposure in rabbits impaired fertility indices [30], and led to testicular degeneration and testosterone suppression [46]. This present study is an extension of our previous studies on [30,46] and data sets were obtained separately.…”
Section: Discussionmentioning
confidence: 56%
“…Although in our previous studies, we demonstrated that oral codeine exposure in rabbits impaired fertility indices [30], and led to testicular degeneration and testosterone suppression [46]. This present study is an extension of our previous studies on [30,46] and data sets were obtained separately. This study demonstrated for the first time that chronic codeine use is strongly associated with poor sperm quality and sperm DNA fragmentation (Figure 4).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Spermatogenesis is initiated when LH from the pituitary activates the Leydig cell to produce testosterone which then acts in conjunction with FSH (O'Shaughnessy, 2014) to stimulate the Sertoli cell relevant in all aspect of spermatogenesis (Jones, 2014) and facilitates germ cells progression to spermatozoa and in the nourishment of developing sperm cells (Griswold, 1998, 2018; Liang et al., 2019). Testicular activities of LDH, ALP and ACP are important in the maintenance of normal germ cell growth and phosphorylative role in glucose usage by germ cells during spermatogenesis (Akhigbe & Ajayi, 2020; Motawi, Sadik, & Refaat, 2010; Rizk, Zaki, & Mina, 2014), while G6PD is essential for providing reducing equivalent necessary for steroidogenesis (Aly & Khafagy, 2014). The decrease in serum testosterone and LH was accompanied by a clear decrease in testicular activities of ALP, ACP, G6PD and LDH in diclofenac‐treated rats signifies impairment in the synthesis or release of hormones and inhibition of marker enzyme activities vital for spermatogenesis (Adedara, Okpara, et al, 2019; Owumi, Ochaoga, Odunola, & Farombi, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Their study demonstrated that although codeine enhances sexual locomotor activity, it reduces copulatory efficiency and percentage fertility index. This is possibly via oxidative/inflammatory and caspase 3‐mediated testicular damage (Akhigbe & Ajayi, 2020). Several studies have reported that opioids induce loss of libido, impotence and infertility in men (Daniell, 2002; Gratzke et al., 2010; Katz & Mazer, 2009; Schlosser, Nakib, Carre‐Pigeon, & Staerman, 2007).…”
Section: Drug Abusementioning
confidence: 99%